Control strategies in enhanced stand-alone mini-grid operations for the NESI–an overview - Balogun, Adeola; Olajube, Ayobami; Awelewa, Ayokunle; Agoro, Sodiq; Okafor, Frank; Sanni, Timilehin; Samuel, Isaac; Ajilore, Adejumoke (Frontiers in Energy Research, 2024)
Diverse control strategies for enhancing operations of isolated distribution grids are reviewed. Such distribution grids are called mini-grids or micro-grids, depending on their power flow capabilities. Robust control schemes identified in other climates for mini-grid and micro-grid operations are yet to be fully explored in the Nigerian electricity supply industry (NESI). Sustainable control strategies suitable for isolated distribution grids in the NESI predicate on capabilities for diverse objectives, such as energy conservation, affordability, efficient power throughput, and utilization, for enhanced resiliency and reliability. Consequently, the distributed control system in hierarchical layers is identified as a suitable choice for mini-grid operations in Nigeria because of its robustness in scalability and in energy conservation. However, the model predictive control (MPC) scheme is observed to be uniquely applicable in all of the hierarchical control layers. Therefore, a cascade-free MPC with improved robustness against sensitivity to system parameter variation is presented at the primary control layer for an H8 voltage source inverter (VSI) used for grid integration of the solar photovoltaic (PV) system. The H8 inverter gives more promising mitigation strategies against common-mode voltage and leakage current. Moreover, the control of DC link voltage for maximum power point tracking (MPPT) is achieved by the H8 inverter, thereby eliminating the need for a separate converter for MPPT. Thus, sustainability is achieved.